Asuhan Kebidanan Ibu Hamil pada Ny.ꞌꞌWꞌꞌ di Pustu Marinding Kecamatan Bajo Barat Kabupaten Luwu - Jumriana Ibriani; Fitriana Ibrahim; Devianti Tandiallo; Mega Indah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Pregnancy is the process of growth and development of an intrauterine fetus starting from conception and ending until the start of labor. The length of pregnancy from ovulation to parturition is around 280 days (40 weeks), and no more than 300 days (43 weeks). This 40 week pregnancy is also called a mature (term) pregnancy. If the pregnancy is more than 43 weeks, it is called postmature pregnancy. Pregnancy between 28 and 36 weeks is called premature pregnancy. The aim of this research is to implement pregnancy midwifery care for Mrs